Spatial-Temporal Dimensions of Efficiency among Electric Cooperatives in the Philippines - Rouselle F. Lavado; Erniel B. Barrios (Philippine Institute for Development Studies (PIDS), 2008)
The efficiency of 119 electric cooperatives in the Philippines from 1990 to 2002 is analyzed using a stochastic frontier model augmented with spatial-temporal terms, addressing the underestimation of technical efficiency usually encountered among maximum-likelihood based methods. The model is also robust to the choice of environmental variables that will be included in the inefficiency equation provided that the spatial distance measure substantially captures the efficiency-enhancing factors. The average of estimated technical efficiency is 0.86. The growth in technical efficiency of 1-2% per year is explained by the slow adjustment process in the operation of the cooperatives lacking the medium to feedback production outcomes in the previous year to their operation cycle in the following year. Medium-sized cooperatives need to organize for strategic competitive advantage and to facilitate attainment of production efficiency.
Keywords: C21; C23; C51; D24; 330; technical efficiency; stochastic frontier; electric cooperative; spatial externalities